Implementasi Metode Six Sigma untuk Mengurangi Produk Cacat pada Produk Garam Halus Yodium - Alfarisy, Mohammad Rian; Abi Hanif Dzulquarnain (Journal of Trends Economics and Accounting Research, 2023)
PT GARAM Segoromadu is a manufacturing company engaged in the salt sector located in Gresik, East Java. The company produces iodized fine salt and non-iodized fine salt. The problem that still occurs at PT GARAM Segoromadu is that there are still product defects in iodized fine salt. Defects that occur such as dirty, blackspot, and mamel. The method used is the Six Sigma method. The purpose of this research is to implement the Six Sigma method to reduce product defects in iodized fine salt. Six Sigma is a tool used to fix problems and improve quality through the DMAIC cycle (Define, Measure, Analyze, Improve, Control). From the calculation results obtained a decrease in DPMO from 20,061 tons with a level of 3.57 sigma to 13,332 tons with a level of 3.72 sigma.